2009
DOI: 10.1271/bbb.80854
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Activity of a Leaf Extract Prepared fromSalacia reticulatain Mice

Abstract: The effects of a water extract prepared from the leaves of Salacia reticulata on the absorption of sugars in normal and type 1 diabetic mice were investigated. The simultaneous oral administration of the extract at a dose of 1.0 mg/mouse with maltose or sucrose inhibited the postprandial elevation of the plasma glucose and insulin levels and intestinal alpha-glucosidase activities in mice. In addition, the supply of a 0.01% solution of the extract as drinking water prevented the elevation of the plasma glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
1
20
1
2
Order By: Relevance
“…Although the functions of KT stems and roots extracts have been actively studied, the functions of KT leaves have never been studied. Accordingly, our previous study showed that the aqueous extracts of KT leaves inhibited α‐glucosidase activity and decreased the plasma glucose levels of mice (Yoshino and others 2009). In the present study, the PLI activity of KT leaf extracts was evaluated and compared with that of KT stems extracts.…”
Section: Introductionsupporting
confidence: 62%
“…Although the functions of KT stems and roots extracts have been actively studied, the functions of KT leaves have never been studied. Accordingly, our previous study showed that the aqueous extracts of KT leaves inhibited α‐glucosidase activity and decreased the plasma glucose levels of mice (Yoshino and others 2009). In the present study, the PLI activity of KT leaf extracts was evaluated and compared with that of KT stems extracts.…”
Section: Introductionsupporting
confidence: 62%
“…Coscinium sps., and Salacia sps. were reported for their anti-diabetic and anti-inflammatory activities (Nayak et al, 2013;Ravishankar et al, 2013;Yoshino et al, 2009;Ismail et al, 1997). Chloroxylon sps., Cayratia sps.…”
Section: Introductionmentioning
confidence: 99%
“…[2324252627] Blocking of carbohydrate breakdown in the intestinal tract by various herbs such as Pelvetia , tochu-cha, welsh onion, and clove are well documented in the published literature. [28] Several clinical trials have been conducted in the past to determine the efficacy of herbal formulations that lower post-prandial blood sugar levels. [2930] Although popularity of herbal medicine is increasing, systematic reviews of scientific reports on the therapeutic usefulness and safety profile of herbal medications suggest the necessity of adequate data still to be generated on this aspect.…”
Section: Discussionmentioning
confidence: 99%